2012
DOI: 10.1073/pnas.1207308109
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant solution for pandemic influenza vaccine production

Abstract: Extensive preparation is underway to mitigate the next pandemic influenza outbreak. New vaccine technologies intended to supplant egg-based production methods are being developed, with recombinant hemagglutinin (rHA) as the most advanced program for preventing seasonal and avian H5N1 Influenza. Increased efforts are being focused on adjuvants that can broaden vaccine immunogenicity against emerging viruses and maximize vaccine supply on a worldwide scale. Here, we test protection against avian flu by using H5N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 32 publications
(36 reference statements)
3
67
0
Order By: Relevance
“…GLA adjuvant formulations have been used with experimental vaccines for influenza, HIV (29), respiratory syncytial virus (RSV) (30), leishmaniasis (31), malaria (32), and leprosy (33) in addition to TB (34,35). Many of these vaccines using GLA formulations have also resulted in protection in preclinical animal models, including mice (34)(35)(36), ferrets (37,38), guinea pigs (34,35,39), cotton rats (30), and hamsters (40), against infectious challenge.…”
Section: Et Al Have Shown a Transient Increase In Ifn-␥ From Cd4mentioning
confidence: 99%
“…GLA adjuvant formulations have been used with experimental vaccines for influenza, HIV (29), respiratory syncytial virus (RSV) (30), leishmaniasis (31), malaria (32), and leprosy (33) in addition to TB (34,35). Many of these vaccines using GLA formulations have also resulted in protection in preclinical animal models, including mice (34)(35)(36), ferrets (37,38), guinea pigs (34,35,39), cotton rats (30), and hamsters (40), against infectious challenge.…”
Section: Et Al Have Shown a Transient Increase In Ifn-␥ From Cd4mentioning
confidence: 99%
“…Some influenza virus vaccine adjuvants have been demonstrated to induce cross-protective responses (13,22,45), and cross-protection has been associated with the induction of Th1-type immune responses (47). Therefore, we sought to assay whether 1V270 and 1Z105 could induce heterologous protection from influenza viruses in two different assays.…”
Section: Z105 Enhances Dendritic Cell Maturation and Antigen Presentmentioning
confidence: 99%
“…Avian-origin influenza A viruses of the H5N1 subtype are of concern for their potential to cause a human pandemic with a high mortality rate, and efforts to develop vaccines against H5 subtype avian influenza viruses have demonstrated that H5 subtype HAs are poorly immunogenic and may require the use of an adjuvant (45). Mice were immunized with 2 g of rHA derived from A/Vietnam/1203/2004 (VN/04), a highly pathogenic avian H5N1 subtype virus, plus adjuvant or in vehicle alone (Fig.…”
Section: Z105 Enhances Dendritic Cell Maturation and Antigen Presentmentioning
confidence: 99%
“…One reason for this long gap is that the principles of adjuvant activity were largely unknown; thus, the development of adjuvants was empirical, Moreover, many adjuvants, including Freund's adjuvant, were reactogenic and not acceptable for licensure (2). Recent methods to improve vaccine delivery have taken several approaches, including the use of virosomes (3)(4)(5), vector-based methods (6)(7)(8), liposome-based methods (9)(10)(11), and the use of more traditional formulation with adjuvants (12)(13)(14)(15)(16)(17). Each of these methods has some drawbacks, in terms of reactogenicity, regulatory issues, product stability, or time required for formulation; however, each of these methods focuses on presenting the vaccine as a particulate.…”
mentioning
confidence: 99%